NEW BORN PROJECT MANAGEMENT PHILOSOPHIES (LEAN & AGILE) IN CONSTRUCTION INDUSTRY Case: Construction company x plumbing renovation projects - Lehtiranta, Tommi (My University, 2017)
Project Management in the construction industry has reach the turning point. Traditional project management methodologies have proved to be ineffective. Construction companies have started to seek various project management methodologies to be able to create more customer value. Research is distributed to the several stages. First is theoretical literature review. In a second part the secondary research results has been researched to be able to find relative success factors. The third part constructs from a case study from a Finnish plumbing renovation projects. The main case is the plumbing renovation project made of Company X who were able to reduce project duration significantly. The object for the research was to find project management a success factors on construction industry and in Finnish plumbing renovation projects. Secondary empirical study opened key factors in construction business and case study how the projects is managed at the moment, and how the project management could be developed in the future.
Keywords: Project management; agile; lean; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|